Low cost carrier growth in the US airline industry: Past, present, and future - Harumi Ito; Darin Lee (Brown University, Department of Economics, 2003)
This paper documents the growth of low cost carriers (LCCs) in the U.S. airline industry since 1990. By estimating simple probit models, we quantify the market characteristics which have influenced nonstop LCC entry in 351 city-pair markets over the past decade. We confirm that pre-entry market density is the single most important factor influencing LCC entry into a city-pair market. For each of the large-hub-and-spoke carriers, we quantify their past, present and future exposure to LCCs. In particular, we predict which markets currently not served by LCCs are the most likely to be entered in the future. Finally, we predict the proportion of network carrier revenue that may ultimately be exposed to nonstop LCC competition. – Airlines ; Market Entry ; Deregulation
Keywords: L11; L93; 330; Luftverkehr; Niedrigpreisstrategie; Markteintritt; Wettbewerb; USA; Probit-Modell